Impact of pharmacotherapy follow up in the health-related quality of life of patients with - Ayala L, Liana K. (2010)
Was evaluated the impact that generates the intervention of the pharmacist in the health-related quality of life HRQL patients with diagnosis of essential arterial hypertension (AHT). They was from external doctor’s offices of the Cardiology Service and they received their medicines through the Chronic Patients Drugstore of the Navy Medical Center “Cirujano Mayor Santiago Távara”, during a period of six months, using the Dáder method of pharmacotherapy follow-up (PTF). 14 patients of 40 years old to more were included in the study, 71,4% were men and 28,6% women without another associate chronic pathology. Specific MINICHAL questionnaire was used in order to determine the HRQL to the beginning of the study, during and later of pharmaceutical intervention. It was detected 29 drug-related problems (DRP): 66% of them related mainly to the necessity, 24% to effectiveness and 10% to security. Were solved 24 drug related problems (DRPs), (75%) that demonstrates the degree of acceptance of the pharmaceutical recommendations to eliminate the causes of DRPs and justify the incorporation of the PTF as essential part in the function of the hospital pharmacist. The communication of the interventions were done in major percentage between pharmacist-patient (87,5%), using both the verbal form as the written one, and pharmacist-patient-phycicians (12,5%) using the written form. At the end of the study, 57% of the patients had controlled their arterial pressure, in comparison with 42% of the patients at the beginning of the study. Was conclude that the HRQL is positively influenced by pharmacist intervention through PTF.